The up-regulation of TGF-β1 by miRNA-132-3p/WT1 is involved in inducing leukemia cells to differentiate into macrophages - Zhimin Wang; Chaozhe Wang; Danfeng Zhang; Xidi Wang; Yunhua Wu; Ruijing Sun; Xiaolin Sun; Qing Li; Kehong Bi; Guosheng Jiang (PLoS ONE, 2025)
Although it has been shown that abnormal expression of Wilm’s tumor gene 1 (WT1) is associated with the occurrence of leukemia, the specific mechanism via which it induces leukemia cells to differentiate into macrophages remains poorly understood. Based on the prediction that the microRNA miRNA-132-3p is the miRNA that possibly lies upstream of the WT1 gene, we hypothesized that miRNA-132-3p may participate in the polarization process of macrophages through regulating expression of the WT1 gene. The focus of the present study was therefore to investigate the role of the miRNA-132-3p/WT1 signaling axis in the differentiation of THP-1 leukemia cells into macrophages induced by PMA. The results obtained indicated that, compared with the control group, the proliferation of THP-1 cells was clearly inhibited by PMA, and the cell cycle was arrested at G0/G1 phase, associated with an upregulation of CD11b and CD14 expression. Induced by PMA, the expression level of miRNA-132-3p was increased, WT1 expression was decreased, and the expression level of TGF-β1 was increased. Following transfection with miRNA-132-3p mimics, however, the expression of WT1 in the THP-1 cells was downregulated, with upregulation of the CD11b and CD14 antigens, whereas this downregulation of WT1 mediated by miRNA-132-3p mimics could be reversed by co-transfection with WT1 vector, which was accompanied by downregulation of the CD11b and CD14 antigens. The luciferase activity of the co-transfected miRNA-132-3p mimic + WT1-wild-type (WT) group was found to be statistically significantly lower compared with that of the co-transfected miRNA-132-3p mimic + WT1-mutated (MUT) group. Furthermore, chromatin immunoprecipitation experiments showed that WT1 was able to directly target the promoter of the downstream target gene TGF-β1, which led to the negative modulation of TGF-β1 expression, whereas downregulation of WT1 led to an upregulation of the expression of TGF-β1, which thereby promoted the differentiation of THP-1 cells into macrophages. Taken together, the present study has provided evidence, to the best of the authors’ knowledge for the first time, that the miRNA-132-3p/WT1/TGF-β1 axis is able to regulate the committed differentiation of leukemia cells into macrophages.